2022
DOI: 10.3390/ijerph192013496
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Associations between Social Media Addiction and Depression: Attentional Bias as a Mediator and Socio-Emotional Competence as a Moderator

Abstract: Social media is used daily by a significant number of young people and can have an important influence on the well-being of its users. The aim of this study was to determine the motives for social media use among Chinese youth and whether social media addiction associates with depression. Another objective was to analyze possible mediating and moderating effects in explaining the association between social media addiction and depression. Participants were 1652 secondary school students (51.5% boys and 48.5% gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 53 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…This positive relationship was also confirmed during the COVID‐19 pandemic (Moniri et al, 2022). Direct evidence from experimental studies has also confirmed this positive association (Xiao et al, 2022). For example, Hu et al (2020) found that individuals with high levels of smartphone addiction have an attentional bias toward negative emotional information and that these participants show more initial fixations and longer initial fixation durations on negative emotional faces.…”
Section: Introductionmentioning
confidence: 74%
“…This positive relationship was also confirmed during the COVID‐19 pandemic (Moniri et al, 2022). Direct evidence from experimental studies has also confirmed this positive association (Xiao et al, 2022). For example, Hu et al (2020) found that individuals with high levels of smartphone addiction have an attentional bias toward negative emotional information and that these participants show more initial fixations and longer initial fixation durations on negative emotional faces.…”
Section: Introductionmentioning
confidence: 74%
“…As association does not equal causation, whether internet addiction disrupts their participation in social networks thereby making these adolescents more vulnerable to be bullied, or whether these adolescents have personalities that make them more likely to play video games and are more likely to be bullied, could all become testable hypotheses. A growing body of literature highlighted the linkage between internet addiction and bullying victimization through adult attachment, deficiency in social competency, attentional bias, hyperactivity, and social isolation [34][35][36]60,61], and provided cues for actions. Multiple countermeasures were feasible, for example, improving coping strategies for adolescents has demonstrated its utility to reduce bullying victimization [62].…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents with internet addictions might have developed compulsive and problematic social and emotional habits, experienced disruptive peer relationships and restricted social participation, consequently leading to bullying victimization [34]. Moreover, the impaired socioemotional competencies in adolescents with internet addiction may also have a detrimental effect on their mental health [35], possibly through attentional bias towards negative information [36], then perhaps leading to bullying victimization in adolescents [37]. Although emerging studies have recently attempted to explicate the linkage between these behaviors, evidence is lacking with respect to the joint contributions of internet addiction and depression to bullying or polybullying victimization.…”
Section: Introductionmentioning
confidence: 99%
“…The other perspective suggests that the Internet possesses a substitution effect, which is not conducive to the formation of a healthy lifestyle for older adults. Social withdrawal and impaired psychological wellbeing, such as depression and loneliness, invariably come with Internet addiction [19,20], ultimately leading to an unhealthy lifestyle. In conclusion, this study proposes the first hypothesis: H1 More frequent digital use is associated with a healthier lifestyle among Chinese older adults.…”
Section: Introductionmentioning
confidence: 99%